»Vater, in deine Hände übergebe ich meinen Geist«: das Kreuzeswort Jesu in Lk 23,46 und die Rezeption von Ps 31,6 im frühen Judentum und Christentum - Dochhorn, Jan (Early christianity, 2011)
The last words of Jesus in Luke 23:46 are not – as often stated in secondary literature – the night prayer of a pious Jew, but build upon a reading of Ps 31:6, which was wide-spread in Early Judaism: In Jewish literature contemporary to the Gospel of Luke, Ps 31:6 was generally associated with the death of the righteous one, who in that moment, especially when persecuted, handed over his soul to God. Ps 31:6 was thereby also interpreted in the light of a dichotomous anthropology; giving the concept of a general body/soul dichotomy a biblical foundation was one of the functions of this verse.